Die Stundentexte zu Seiten der Nut auf der Innenseite des Deckels des inneren Sarges Milano E 0.9.40147 eines Peftjau(em)auuiaset - Graefe, Erhart (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
Publication of the inner face of the cover of the inner coffin Milano E 0.9.40147 belonging to an untitled . It contains short awakening-texts for the sake of Osiris (e. g., the owner of the coffin) arranged as the 12 hours of day and night. The hours are represented as kneeling goddesses in adoration bearing a sun-disk on their heads for the day or a star for the night. The texts of both sides are of different types, the hours of the day being called “embodiment” of Horus and those of the night “doors”. The composition is the same as on the sarcophagi of the Napatan kings Anlamani and Aspelta. To date the version from the Milano coffin has only been dealt with en passant.